Implementation of the remote indigenous community empowerment program on the sustainability of the local food crops in West Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Indow L, Maturbongs RA, Prabawardani S, Hendri, Lyons G. 2021. Implementation of the remote indigenous community empowerment program on the sustainability of the local food crops in West Papua, Indonesia. Biodiversitas 22: 5247-5254. An ethnobotanical study of local food crops in the areas receiving the program of remote indigenous community empowerment (RIC) in the three ecosystem areas of Domberai, West Papua was conducted to assess the effect of the program on specific local food crops. This study used a descriptive method with qualitative and quantitative data components. Surveys and field observations were carried out at predetermined village locations, using a purposive sampling interview method with community representatives, tribal chiefs, and leaders in each indigenous community. Field data were analyzed quantitatively to find the value of the benefit index (BI) on food crops. Results of the study showed the highest BI values of carbohydrate-rich crops were banana (Musa sp.) which accounted for 98%, sweet potato (Ipomoea batatas) 98%, followed by taro (Colocasia esculenta) 94%, and cassava (Manihot esculenta) 90%. Vegetable crops with the highest BI values were gedi leaves (Abelmoschus manihot) 98%, papaya leaves (Carica papaya) 86%, followed by sweet potato leaves (Ipomoea batata) 56%, cassava leaves (Manihot esculenta) 56%, gnetum leaves (Gnetum gnemon) 55%, and pumpkin leaves (Cucurbita) 52%. The highest BI values in fruit crops were rambutan (Nephelium lappaceum) 72%, mango (Mangifera indica) 70%, and durian (Durio zibethinus) 59%. The shift from local food crops to rice has been observed in the villages of Sakumi and Yamboi which are relatively accessible for transportation, while the people of Watitindoi Village, which is located on a small island and is isolated, have been mostly relied on local food crops.
Keywords: Ethnobotany, Local Food Crops, Remote Indigenous Community, West Papua